Analisis Kualitas Pelaporan Keuangan dalam Upaya Meningkatkan Akuntabilitas Laporan Keuangan di Puskesmas Bantargadung - Eki Rahmattuwloh; Acep Suherman; Iqbal Noor (AKUNTANSI 45, 2024)
This research was conducted to determine the quality of financial reporting and the level of accountability of financial reports at the Bantargadung Community Health Center, Sukabumi Regency. This research uses a qualitative method using an associative descriptive approach. The results of this research show that the Bantargadung Community Health Center has implemented Government Accounting Standards (SAP) in preparing its financial reports, but in preparing its financial reports the Bantargadung Community Health Center lacks human resources from accounting personnel so that the level of accountability in the financial reports at the Bantargadung Community Health Center is less than optimal.